Meningkatkan Motivasi Belajar Siswa pada Pelajaran PAI (Ismuba) Berbasis Kurikulum Merdeka: Studi Kasus di MA Muhammadiyah Yogyakarta - Mohammad Jailani (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2024)
The purpose of this research is to analyze the effect of redesigning the Integrative-Holistic ISMUBA curriculum based on the Curriculum Merdeka (Independent Curriculum) on the improvement of students' learning motivation at MA Muhammadiyah Yogyakarta. The research subjects involve teachers and students. This study uses a qualitative method with a field study approach. The research procedures include observation, interviews, and documentation. The results of the study indicate that there was a 70% increase in students' learning motivation in the second semester. This is due to the implementation of the concept of independent learning, which provides space and time for students to learn independently. The learning approach supported by the platform and the redesign of the ISMUBA curriculum based on the independent curriculum is an initiative of the Ministry of Education, Culture, Research, and Technology (KEMENDIKBUD), the Education and Culture Office of the DIY Region, and the Education and Culture Office of the Central Leadership of Muhammadiyah. This initiative has been able to develop the creativity of ISMUBA teachers and school management in organizing learning. However, there are several inhibiting factors that need to be considered, such as the assumption that the curriculum often undergoes changes and the absence of a curriculum that supports the concept of independent learning before it is introduced. This research will have broad implications for the development of the redesign of the Islamic Education (Ismuba) curriculum, especially in terms of learning and curriculum development at the school and Muhammadiyah Madrasah levels.